التهاب الملتحمة الجرثومي عند الوليد خبرة مشفى الأسد الجامعي باللاذقية - الحكيم, مأمون; ديب, غزل; مسالمة, ماهر (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة (58) حالة إلتهاب ملتحمة عند الولدان المراجعين لمشفى الأسد الجامعي في اللاذقية منها (37) حالة التهاب ملتحمة مكتسب خارج المشفى و(21) حالة التهاب ملتحمة مكتسب داخل المشفى وكانت نتائج هذا البحث كمايلي : وسطي عمر الوليد عند بدء ظهور أعراض التهاب الملتحمة المكتسب خارج المشفى 5.2 يوم و6.3 يوم بعد قبول الوليد داخل المشفى البدء الباكر (خلال الأسبوع الأول) لظهور الالتهاب خارج المشفى 67.6% و61.9% خلال الأسبوع الأول من قبول الوليد داخل المشفى نسبة الذكور الى الاناث 1:1.32 أهم العوامل المؤهبة لالتهاب الملتحمة خارج المشفى وداخلها هو عدم تطبيق الوقاية العينية بالإضافة إلى تطبيق وسائل الإنعاش والخداجة كانت نسبة درجة التهاب الملتحمة الخفيف الشدة 83.7% من الحالات المدروسة خارج المشفى و85.7% للحالات المدروسة داخل المشفى الالتهاب أحادي الجانب في 51.3% من الحالات خارج المشفى و57.2% من الحالات المدروسة داخل المشفى أهم التظاهرات السريرية العينية الإحتقان الملتحمي وتبلغ نسبته 100% والرمص ونسبته تقريبا 85% الاصابات المرافقة خارج العينية تشمل أعراض تنفسية علوية بنسبة 16.2% من حالات التهاب الملتحمة خارج المشفى وأنتان دم ونسبته 66.6% من الحالات داخل المشفى نسبة الاختلاطات العينية 0% نسبة إيجابية الزروع الجرثومية لإلتهاب الملتحمة خارج المشفى 81.1% أما داخل المشفى كانت 76.2% أشيع الجراثيم المسببة لالتهاب الملتحمة خارج المشفى هي: العنقوديات المذهبة 36.6% ثم العصيات الزرق 23.3% ثم الإيشريشيا كولي 20% أشيع الجراثيم المسببة لإلتهاب الملتحمة داخل المشفى العصيات الزرق 31.2% ثم الكليبسيلا 25% ثم العنقوديات المذهبة 18.7% تظهر العصيات الزرق حساسية عالية للأميكاسين والإيميبنم 91.9% ثم السيفتازيديم والسيبروفلوكساسين تمتلك العنقوديات المذهبة نسبة عالية من الحساسية على السيبروفلكساسين ثم الأموكسسيللين- كلافولانيك أسيد والكلوكساسلين الكلبسيلا معندة على أغلب الصادات باستثناء الإيميبنم والسيبروفلكساسين تمتلك كل من الأميكاسين والإيميبنم والسيفوتاكسيم والسفترياكسون فعالية جيدة تجاه الايشريشيا كولي والأنتيروباكتر This study included 58 cases of Neonatal Conjunctivitis at Al Assad University Hospital in Latakia. 37 cases out of the 58 cases were acquired from outside the hospital while the other 21 cases were acquired from inside the hospital. The results were as follows: - The average age of symptoms manifestation in neonates infected is 5.2 days for conjunctivitis acquired outside the hospital and 6.3 days for conjunctivitis acquired inside the hospital starting from the first day of admitting the neonate to the hospital. - The percentage of early onset of neonatal conjunctivitis during the first week in cases acquired outside the hospital was 67.6% while it was 61.9% for neonates acquiring conjunctivitis inside the hospital within the first week of admittance. - Male to female rate was 1.32:1 - The most important predisposing factor, inside and outside the hospital, was the absence of ophthalmic prophylaxis, Resuscitation and Prematurity. - The percentages of mild cases were 83.7% for outpatients and 85.7% for inpatients. - Unilateral neonatal conjunctivitis was 51.3% for outpatient's cases and 57.2% for inpatients cases. - The most important ophthalmic clinical manifestations were conjunctival congestion in 100% and purulent discharge in 85%. - The associated extra ophthalmic manifestations were upper respiratory tract symptoms in 16.2% of cases acquired outside the hospital and sepsis in 66.6% of cases acquired from inside the hospital. - The percentage of ophthalmic complications was 0% - Bacterial culture was positive in 81.1% for cases acquired outside the hospital and 76.2% for cases acquired inside the hospital. - The most common bacterial agents for cases acquired conjunctivitis from outside the hospital were staphylococcus aurus in 36.6%, Pseudomonas aeroginosa in 23.3% and E. coli in 20%. - The most common bacterial agents for cases acquired conjunctivitis from inside the hospital were Pseudomonas aeroginosa in 31.2%, Klebsilla in 25% and Staphylococcus aurus in 18.7%. - Pseudomonas aeroginosa showed high sensitivity to Amikacin and Imipenem 91.9% then comes the Ceftazidime and Ciprofloxacin. - Staphylococcus aurus showed a high sensitivity to Ciprofloxacin, Amoxicillin-Clavulanic acid and Cloxacillin. - Klebsilla was resistant to most of the antibiotics except for Imipenem and Ciprofloxacin. - Amikacin, Imipenem, Cefotaxime and Ceftriaxone have good efficacy against E.coli and Enterobacter.